2018
DOI: 10.5888/pcd15.170225
|View full text |Cite
|
Sign up to set email alerts
|

Hours Lost to Planned and Unplanned Dental Visits Among US Adults

Abstract: IntroductionPoor oral health is associated with lost hours at work or school, which may affect a person’s productivity. The objective of our study was to estimate work or school hours lost to dental visits among adults aged 18 and older by the types of visits (emergency or unplanned; routine, planned, or orthodontic; or cosmetic) and to determine the factors associated with hours lost.MethodsWe used the most recent Oral Health Supplement data, from the 2008 National Health Interview Survey (NHIS), to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Pain from decayed teeth can reduce work productivity and disrupt one’s daily schedule due to loss of focus and the need to visit a dentist for treatment [ 38 , 39 ]. In the United States of America, over 300 million school or working hours were lost annually due to oral problems such as toothache [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain from decayed teeth can reduce work productivity and disrupt one’s daily schedule due to loss of focus and the need to visit a dentist for treatment [ 38 , 39 ]. In the United States of America, over 300 million school or working hours were lost annually due to oral problems such as toothache [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many of individuals still go to work and carry out daily activities while experiencing an oral pain episode (presenteeism), which can impair their productivity, promote attention loss, irritability, anxiety, and depression, and increase the risk of work-related accidents [ 5 ]. In the US, almost 321 million hours of work and school are lost per year due to dental problems, of which emergency dental treatment accounted for 92.4 million work or school hours [ 31 ]. A Canadian study revealed that individuals lose an average of 3.5 working hours each year due to dental problems, which amounts to 40 million hours per year.…”
Section: Discussionmentioning
confidence: 99%
“…Poor oral health may lead to profound impacts on individuals and wider society. Pain or sepsis,4 lower self-esteem,5 reduced school attendance and poorer educational performance,6 poorer quality of life7 and reduced work productivity8 are all common impacts of oral diseases. There are also significant economic costs associated with dental treatment and lost productivity, amounting to approximately US$544 billion globally in 2015 9.…”
Section: Introductionmentioning
confidence: 99%